2022
DOI: 10.3389/fendo.2022.928752
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Level Is Negatively Associated With Bone Mineral Density in U.S. Children and Adolescents Aged 8-19 Years

Abstract: ContextThe relationship of lead (Pb) exposure with bone health in children and adolescents remains controversial.ObjectionWe aimed to investigate the association of blood lead levels (BLL) with bone mineral density (BMD) in American children and adolescents using data from the National Health and Nutrition Examination Survey (NHANES), 2005-2010.MethodsWe analyzed 5,583 subjects aged 8-19 years (mean age, 13.49 ± 3.35 years) from the NHANES 2005-2010. BLL was tested using inductively coupled plasma mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In a steady state, bone contains about 80%–90% of the total body lead burden [ 32 ]. Cui et al [ 33 ] showed that lead affected the lumbar BMD more than the femur, and that the impact on women was more robust. As mentioned above, the dietary intake of manganese is positively related to the lumbar spine, although one study found that blood manganese exposure was negatively related to BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a steady state, bone contains about 80%–90% of the total body lead burden [ 32 ]. Cui et al [ 33 ] showed that lead affected the lumbar BMD more than the femur, and that the impact on women was more robust. As mentioned above, the dietary intake of manganese is positively related to the lumbar spine, although one study found that blood manganese exposure was negatively related to BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other covariates. Other covariates were chosen based on the published studies [8,24,25]. The variance inflation factor (VIF) was used to detect co-linearity between multiple variables.…”
Section: Plos Onementioning
confidence: 99%
“…Boreham et al reported that a 6.4% reduction in PBM during childhood and adolescence could double the risk of fragility fractures in adulthood [6]. Previous studies indicated that PBM formation could be influenced by genetics, diet and nutrition, physical activity, some diseases, and others [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…E2 and SHBG have been shown to be influenced by various factors, such as insulin, thyroid hormone, and environmental endocrine disruptors, in which heavy metals like lead play an important role (12)(13)(14). Poisoning caused by lead, one of the ten most harmful metals listed by the World Health Organization (WHO), is a serious public health concern (15). Blood lead level (BLL) can be a homeostatic marker of lead exposure (16).…”
Section: Introductionmentioning
confidence: 99%